Metagenomic next-generation sequencing clinches the diagnosis of Legionella pneumonia in a patient with acute myeloid leukemia: A case report and literature review - Niu, Siqiang; Zhao, Limin (Frontiers in Cellular and Infection Microbiology, 2022)
Legionella pneumonia caused by Legionella pneumophila is a multi-system disease that is a life-threatening, acute, and severe form of pneumonia. L. pneumophila is widespread and the clinical manifestations of Legionella pneumonia are similar to those of typical and atypical pneumonia. Current diagnostic scores and radiologic evidence have limited diagnostic value. Thus, it is likely that many cases of Legionella pneumonia remain unreported. We describe a woman with a medical history of acute myeloid leukemia who suffered from repeated fever, and no relief following initial empirical antibiotic treatment. Ultimately, she was diagnosed with Legionella pneumonia based on metagenomic next-generation sequencing (mNGS). We also performed a systematic review of the literature and identified 5 other patients who were diagnosed with Legionella pneumonia using mNGS, and reviewed their clinical characteristics, biological characteristics, epidemiological features, laboratory results, clinical findings, and treatments. This literature review showed that accurate etiological diagnosis is becoming increasingly essential for a definitive diagnosis and treatment strategies. The clinical manifestations of Legionella pneumonia are non-specific, and many routine laboratory diagnostic tests cannot identify Legionella. mNGS, an indispensable approach for identifying microorganisms, can provide a promising tool for the rapid and accurate etiological diagnosis methods contributing to early diagnosis, early treatment, and improved prognosis, especially for uncommon species such as L. pneumophila.